Effectiveness of Epoxy Coating on Metal Surfaces of NEW773CAT Heavy Equipment Units - Agus Subeno; Angga Setiawan; Toni Okviyanto; Herlin Sumarna; Dibyo Setiawan; Fauzi Widyawati (Universitas Negeri Jakarta, 2026)
This study investigates the effectiveness of the epoxy coating system on NEW773CAT heavy equipment unit operating in a mining environment. The research primarily focuses on the influence of surface preparation methods, dry film thickness (DFT), and coating type on corrosion resistance and adhesion strength. Field case studies, thickness measurements, and visual inspections were employed to assess the performance of coating system. The results reveal that average coating thickness of 396 μm significantly exceeds the minimum ISO 12944 category C5-I standard, which specifies a DFT of 320-400 μm for high corrosivity environments. The surface preparation process using high-pressure cleaning and power tool cleaning (ST 3.0) was found to produce an ideal substrate for epoxy coating application. The use of high-built epoxy mastic as the primer and Aliphatic Polyurethane as the top coat demonstrated excellent corrosion protection and optimal interlayer adhesion. The spray application technique resulted in a uniform coating with no visible defects. This study emphasizes the importance of combining effective surface preparation and precise coating specifications to ensure long-term protection of metal surfaces in harsh environments. The findings suggest that epoxy coating systems, when correctly applied and prepared, can provide robust protection against corrosion, extending the service life of heavy equipment exposed to aggressive conditions like those found in mining operations.